Comparative Study of Nutritional Status of Beneficiaries and Non-Beneficiaries of Primary School Feeding Programme in Akwa Ibom State - I. O. , Ekumankama; O. M., Umoetuk (Journal of Home Economics Research, 2024)
This study compared nutritional status of beneficiaries and non-beneficiaries of primary school feeding programme in Akwa Ibom State. Specifically, it determined the differences in anthropometric measurements of weight - for – age; height - for – age; and body mass index - for - age of children benefiting and those not benefiting from school feeding programme in Akwa Ibom State. The study adopted a cross- sectional descriptive survey design. The population for the study comprised 818,588 public primary school children ( 3 - 11 years ). Questionnaire and anthropometric measures were used to collect data. Data were analyzed using frequencies and percentages. Data from the anthropometric measurement of pupils (weight-for-age, height-for-age and BMI-for-age) were analysed using WHO anthro plus software. The result was interpreted using Z-score (WHO Standard) and expressed in frequencies and percentages. Chi - Square test result showed that the weight-for-age (X2 =13.437a, P=0.00), height-for-age (X2 = 7.736a, P= 0.02) and BMI-for-age (X2 = 10.281a, P= 0.04) status of the beneficiaries of school feeding programme were comparable to the non beneficiaries at 0.05 level of significance. Thus, the three null hypotheses were accepted for all the parameters tested. In conclusion, school feeding programme has the potential to directly address malnutrition if it is effectively managed. The study recommended among others that Home Economists, Nutritionists and Dieticians should, in conjunction with the government undertake regular monitoring and evaluation of the programme to ensure that adequate and nutritious meals are served.